(untitled) (Anwer Khan Modern Medical College Journal, 2019)
Sarcoidosis is a chronic granulomatous disorder of unknown etiology, commonly affecting the lungs, skin and eyes. Although lungs and lymph nodes are involved in more than 90% of patients, virtually any organ can be involved. We describe a 36 years old lady presented with fever, skin rashes, cough, polyarthralgia, bodyache, wt. loss for 3 months. Examination revealed Fever, Erythema Nodosum, Cervical Lymphadenopathy. Investigations revealed high ESR (80 mm in 1st hour), high CRP, Hilar Lymphadenopathy on Chest X ray, Non-caseous Granuloma, Giant cell and Asteroid body on Lymph node Biopsy. All of her history, clinical examinations and Investigations are suggestive of Sarcoidosis. With symptomatic treatment and watchful observation, now she is completely symptoms free and leaving a healthy life. Anwer Khan Modern Medical College Journal Vol. 10, No. 1: Jan 2019, P 92-95